Transformation of Organo-Modified Thin Plate-Shaped OCP to Laminated Hexagonal HAP Nanocrystals - Mishra, Shiv Prakash (New Innovations in Chemistry and Biochemistry Vol. 5, 2021)
The formation of laminated hexagonal thin plate-shaped hydroxyapatite (HAP) nanocrystals from organically salt of dicarboxylic acid (e.g. succinic acid) based plate-shaped octacalcium phosphate (OCP) under hydrothermal condition which are performed at 180\(^{°}\)C for 3hours. In phase transformation the pH of solution is adjusted at 5.5 with respect of temperature, where complexated succinate ion having Ca/P molar ratio is expected to be 1.56±0.02. The morphological observation of crystals have been characterized by using of XRD, SEM patterns. Since, the HAP crystal system is hexagonally and its crystallite size in the direction of various (a,b,c) axes depending on the plate-shaped HAP crystals thickness. These prepared crystals having their size as perpendicular to the (100) plane with submicrometer thickness is calculated by using of Scherrer’s equation D100 = K\(λ\)/(\(β\) cos\(θ\) ).